Overcoming failure in sport: A self-forgiveness framework - Cowden, R. G.; Worthington, E. L. (Journal of Human Sport & Exercise, 2019)
Within the winner or loser dichotomy that exemplifies competitive sport, athletic success hinges on the ability to overcome and respond constructively to failure. This article introduces self-forgiveness as an adaptive, purposeful approach to coping with competitive sport performance failure in a way that stimulates personal growth and combats loss of motivation. In contrast to defensive responses that shield self-integrity, genuine self-forgiveness is reached through a process in which athletes (a) accept personal responsibility for their role in the unsuccessful performance outcome and (b) restore self-regard by affirming the self. Although athletes expose themselves to uncomfortable emotional experiences associated with failure, self-forgiveness is proposed as a process that enables athletes to objectively evaluate unsuccessful performances, identify areas warranting improvement, and develop adaptive psychological recovery responses to failure.